PENGARUH PEMBERIAN TEH HIJAU TERHADAP PENURUNAN TEKANAN DARAH PADA LANSIA DENGAN HIPERTENSI DI YAYASAN PANTI SOSIAL TRESNA WERDHA PROVINSI MALUKU - Abdul Thalib; Dhamas Mega Amarlita; Kreshas J.A Noija; Wa Ode Defi Milarti (STIKES Pasapua Ambon, 2022)
Introduction : Along with the times, humans tend to adopt a modern lifestyle. This lifestyle greatly affects people’s health. Hypertension is an increase in blood pressure which results in the supply of oxygen carried by the blood experiencing obstacles to the tissues that need it. Objective: To determine the effect of giving green tea on reducing blood pressure in the elderly with hypertension at the Tresna Werdha Social Institution Foundation, Maluku Province. Method: The method used in this study was a pre-experimental design with a one group pretest- posttest design. The independent variable is green tea in November 2021. The sample for this study was selected using the total sampling technique, which consisted of 30 populations. The statistical test used is Wilcoxon α = 0.005. Results: Shows that there is a relationship between the effect of giving green tea on reducing blood pressure in patients with hypertension at the Tresna Werdha Social Institution Foundation, Maluku Province, namely the results obtained are p = 0.000 <0.05. Conclusion: there is an effect of giving green tea on reducing pressure in hypertensive patients at the Tresna Werdha Social Institution Foundation, Maluku Province.